Thermal response of mortar panels with different forms of macro-encapsulated phase change materials: A finite element study - Kong S.Y.; Yang X.; Paul S.C.; Wong L.S.; avija B. (MDPI AG, 2023)
Finite element method; Mortar; Paraffins; Specific heat; Thermoelectricity; Encapsulated phase change materials; Finite-element study; Lower temperatures; Modelling techniques; Numerical investigations; Parametric study; Phase change effects; Thermal response; Phase change materials